Anticorrosive evaluation of Sio2-Tio2-Zro2 ceramic trilayers synthesized by the Sol-Gel method - Bautista Ruiz, Jorge Hernando; Ortiz Otálora, César Armando (Universidad Pedagógica y Tecnológica de Colombia, 2009)
The conformation of trilayers of ceramic coatings of the SiO2-TiO2-ZrO2 system is shown, synthesized by the Sol-gel method, using Si (OC2H5) 4, Ti (OBu) 4 and Zr (OC3H7) 4 as precursors, as EtOH and water, and as a complexing agent 2,4 pentanedione. The ceramic coatings were deposited on AISI / SAE 304 stainless steel substrates using the dip-coating technique. The influence of the coatings on the anticorrosive behavior of the substrate in a 3% HCl solution was studied using Electrochemical Impedance Spectroscopy (EIS) techniques and potentiodynamic polarization curves. Additionally, a morphological study was performed using the Atomic Force Microscopy (AFM) technique. The values of the electrochemical parameters were found to change substantially with the concentration of the precursors added to the effects of the film on the substrate.